Geotropism and Oncogenic Potential of HPV Infections in Cohort Study Populations in Vojvodina, North Region of Serbia - Mandić, Aljoša; Nikolić, Nataša; Maričić, Slobodan; Gutić, Bojana; Stevanović, Nemanja; Bašica, Branka (Scripta Medica, 2023)
Background/Aim: Geotropism of the human papillomavirus (HPV) represents the heterogeneous distribution of different genotypes worldwide. Aim of this study was to evaluate the prevalence of the human papillomavirus (HPV) infection in women from Vojvodina, Serbia, according to cytological status and pathological changes of cervix - dysplasia and cancer. Methods: The research was conducted as a retrospective study at the Oncology Institute of Vojvodina and the Institute of Public Health of Vojvodina (IPHV). Data from the medical records of female patients treated for cervical intraepithelial neoplasia or cervical cancer at the Department of Gynaecology, Clinic for Surgical Oncology, Oncology Institute of Vojvodina in Sremska Kamenica in the period from 2016 to 2021 were used, as well as the laboratory findings of the IPHV for a group of patients with normal cytological results of the Papanikolau (PAPA) smear. Results: A total of 731 women, from 20 to 82 years of age, with different cytological results were enrolled. 567 samples were classified as NILM, while 164 samples belong to a group of abnormal histopathology (LSIL/HSIL/cervical cancer). The HPV genotyping assay was performed using the EUROArray HPV test to detect 30 HPV genotypes. In the overall number with normal cytological findings, HPV infection was verified in 242 (42.7 %) patients, of which 135 (55.8 %) were verified with high risk HPV, while 76 (31.4 %) were verified with a mixed group of HPV (Low risk/High risk HPV). Most prevalent genotypes were HPV 16, 31, 53, 51 and 18 in NILM cytological status. In the samples with the abnormal histopathology, the most prevalent genotypes were HPV 16, 33, 31 and 56, while 18 and 39 were equally verified. Genotype 16 was the most prevalent in the examined sample, with a higher prevalence in higher-grade histopathological findings: 18.8 % in LSIL, 31.9 % in HSIL and 75.0 % in cervical cancer samples. Infection with multiple associated genotypes of HPV was not correlated with histopathology. By comparing histopathological diagnosis and age, older patients had higher-grade lesions. Conclusion: Based on the estimated oncogenic potential of HPV genotypes as well as their prevalence in presented sample, it can be concluded that the nine-valent HPV vaccine for genotypes 6, 11, 16, 18, 31, 33, 45, 52 and 58 would have the potential to prevent HPV infection and the incidence of precancerous lesions and cervical cancer in about 85 % of women. Observing trends in the prevalence of HPV, especially HR HPV genotypes, can be important in the further strategy of applying secondary and primary prevention, as well as the application of HPV detection as part of co-testing or considering the introduction of HPV testing in the initial screening program.